Entrepreneurship and Indian IT outsourcing: the good, the bad, and the money saved - Dossani, Rafiq (Henry Stewart Talks, 2017)
The case study reviews how a semiconductor startup in Silicon Valley outsourced the production of a new type of semiconductor to a technology services company in India in 2002. The case study examines the benefits as well as the problems that both companies experienced during the outsourcing relationship.